(untitled) (Global Journal of Medical Research, 2022)
Background A Cataract is one of the most common disorders affecting the eye and is the leading cause of visual impairment and blindness Patients who are planning for surgery don t have adequate knowledge not prepared for the surgery which results in increase anxiety Aim This study aimed to assess the effectiveness of NLI on the level of knowledge and pre-operative anxiety Method An evaluator approach with Quasi experimental non randomized control group design was adopted for the study The study was conducted on 60 30 each experimental and control group patients using non-probability consecutive sampling technique Result In the experimental group the pre-test mean S D of level of knowledge was 11 5 2 02 were significant difference with post-test mean S D was 21 1 96 In the experimental group the pre-test mean S D of pre-operative anxiety was 84 76 4 95 with post-test mean S D was 40 26 6 75